COLOR CHANGE OF CHINESE FIR THROUGH STEAM-HEAT TREATMENT - Yongjian Cao (BioResources, 2012)
Dark brown wood color is a current trend and widely appreciated by consumers in the furniture and decoration markets. Heat treatment is one of the most effective methods to darken wood’s appearance. The influence of steam-heat treatment on color change of Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.) was investigated within the temperature range from 170 to 230 oC and time from 1 to 5 hours in an air-tight chamber within an atmosphere comprising less than 2 percent oxygen. Saturated steam was used as a heating medium and a shielding gas. The results showed that the chroma difference (△C*) decreased gradually, while the color difference (△E*) and hue difference (△H*) increased with an increase in temperature and length of time. An analysis of variance (ANOVA) and a multi-comparison analysis revealed that the treatment temperature plays a more important role in darkening wood color during the process of steam-heat treatment in comparison with the treatment time. The results suggest that a more desirable wood color can be achieved with the technology of steam-heat treatment.